A Sociological Study of Literature on the Poetry Anthology 'Selama Laut Masih Bergerlombang' by Mariati Atkah: Coastal Life, Culture, and Life Transitions - Fitri Kamisah; Arini Putri Safira; Elsa Maharani; M. Fadillah Anugrah; Elmustian (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to examine the representation of coastal community life in the poetry anthology "Selain Laut Masih Bergelombang" by Mariati Atkah through a sociology of literature approach. The sociology of literature approach is used to explore the relationship between literary works and the social conditions that form the background of their birth. This study uses a qualitative descriptive method commonly used in social science research, including research in the field of literature. The main data source of this study is the poetry texts contained in the poetry anthology "Selain Laut Masih Bergelombang". Data on the representation of coastal community life in the poetry anthology "Selain Laut Masih Bergelombang" were collected using an observation guide instrument validated by time triangulation assisted by a checklist. The research data were analyzed thematically. The results of the study indicate that this work displays various aspects of coastal community life that are full of meaning, such as perseverance in work, social intimacy, a spirit of togetherness, and local wisdom that grows from human closeness to the sea. In addition, this anthology also depicts social changes that occur due to the influence of modernization, which has an impact on shifting traditional community values. Overall, “Selain Laut Masih Bergelombang” not only has aesthetic value, but also functions as a cultural, social, and spiritual reflection of the lives of Indonesian coastal communities.